2006
DOI: 10.1253/circj.70.1655
|View full text |Cite
|
Sign up to set email alerts
|

Open Heart Operation in a Child With Congenital Heart Disease and Hereditary Spherocytosis

Abstract: ereditary spherocytosis (HS) is a genetically determined red blood cell membrane disorder that results in hemolytic anemia. 1 There are only a few case reports of patients with HS who have undergone open heart surgery. [2][3][4][5][6][7][8][9] Theoretically, these patients have a high risk of perioperative hemolysis and secondary renal dysfunction attributable to the deleterious effects of cardiopulmonary bypass (CPB). Because limited information is available concerning such operations for patients with HS, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…A literature review gives only a few congenital heart disease cases with hereditary spherocytosis undergoing open‐heart surgery (Table 2). 2–6 Our case is the only reported infant with hereditary spherocytosis to undergo open‐heart surgery.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A literature review gives only a few congenital heart disease cases with hereditary spherocytosis undergoing open‐heart surgery (Table 2). 2–6 Our case is the only reported infant with hereditary spherocytosis to undergo open‐heart surgery.…”
Section: Discussionmentioning
confidence: 80%
“…Kawahira et al 3 reported a 15‐month‐old child who underwent open‐heart surgery without a previous splenectomy, and they conclude that splenectomy before cardiac operations in children with HS may not always be necessary. Use of non‐ionic antihemolytic detergent poloxamer 188 and haptoglobin has been reported 2,3,5 . Poloxamer 188 protects the red cell membrane and prevents the increase of serum‐free hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Although HS occurs as often as in 1 in 2000 people (1), there is surprisingly little published about HS management during open heart surgery. We found only 21 reported cases of which only 7 (Table 2) were less than 18 years of age at the time of surgery (2–8). There were no reports of patients with HS undergoing heart transplantation.…”
Section: Discussionmentioning
confidence: 89%
“…The risk for hemolysis during CPB in patients with HS is largely theoretical. A variety of approaches have been advocated for HS patients requiring cardiac operation including avoidance of cardiopulmonary bypass, pre‐emptive splenectomy (9), administration of haptoglobin to reduce plasma free hemoglobin (3,4,8), using poloxamer 188 (a non‐ionic antihemolytic detergent that protects RBC membranes during CPB) (8), or simply proceeding with surgery employing CPB without any special measures (2,5,7). No significant hemolysis or renal failure occurred in any of these reports.…”
Section: Discussionmentioning
confidence: 98%
“…There is much argument and uncertainty about the benefits or risks of corrective surgery of the underlying anatomical defect. 3, 4 It is unclear why some patients undergoing complete repair or palliative surgery of the CHD still develop irreversible PAH. The pathological mechanisms of pulmonary vasculopathy are poorly understood in patients with irreversible PAH secondary to CHD.…”
mentioning
confidence: 99%